Simplifying
3 + 2(x + -6) + 5 + -3(x + 4) = 6x
Reorder the terms:
3 + 2(-6 + x) + 5 + -3(x + 4) = 6x
3 + (-6 * 2 + x * 2) + 5 + -3(x + 4) = 6x
3 + (-12 + 2x) + 5 + -3(x + 4) = 6x
Reorder the terms:
3 + -12 + 2x + 5 + -3(4 + x) = 6x
3 + -12 + 2x + 5 + (4 * -3 + x * -3) = 6x
3 + -12 + 2x + 5 + (-12 + -3x) = 6x
Reorder the terms:
3 + -12 + 5 + -12 + 2x + -3x = 6x
Combine like terms: 3 + -12 = -9
-9 + 5 + -12 + 2x + -3x = 6x
Combine like terms: -9 + 5 = -4
-4 + -12 + 2x + -3x = 6x
Combine like terms: -4 + -12 = -16
-16 + 2x + -3x = 6x
Combine like terms: 2x + -3x = -1x
-16 + -1x = 6x
Solving
-16 + -1x = 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
-16 + -1x + -6x = 6x + -6x
Combine like terms: -1x + -6x = -7x
-16 + -7x = 6x + -6x
Combine like terms: 6x + -6x = 0
-16 + -7x = 0
Add '16' to each side of the equation.
-16 + 16 + -7x = 0 + 16
Combine like terms: -16 + 16 = 0
0 + -7x = 0 + 16
-7x = 0 + 16
Combine like terms: 0 + 16 = 16
-7x = 16
Divide each side by '-7'.
x = -2.285714286
Simplifying
x = -2.285714286
Hope this helps!